Insect repellents handbook - Debboun, Mustapha; Frances, Stephen P.; Strickman, Daniel (CRC press, 2014)
This book provides an update of the first edition, which is recognized as the definitive reference on insect repellents. The Second Edition reflects the current state of insect repellent science. It covers the processes involved in the development and testing of new active ingredients and formulations, and discusses the practical uses of repellents. It is a resource that will be useful to a wide variety of professionals including insect repellent researchers, medical entomologists, public health and medical personnel, industry and sales professionals, government regulators, and wildlife scient.
CRC Press is an imprint of Taylor & Francis Group.
Keywords: Insect baits and repellents.; elektronické knihy; electronic books